Review Of Ethics And Waiter Responsiveness In Breakfast Service At Mentawai Restaurant Hotel Pangeran Beach Padang - Pratama, Rizqi Flantika; Kasmita, Kasmita (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
This research was motivated by several complaints from guests regarding the ethics and responsiveness of waiters while on duty at the Mentawai Restaurant Hotel Pangeran Beach Padang. This research aims to analyze the ethics and responsiveness of waiters in breakfast service at the Mentawai Restaurant Hotel Pangeran Beach Padang. This research is useful as considerations and suggestions regarding waiter ethics and responsiveness.This research method is descriptive quantitative. The population in this study were all guests staying at the Pangeran Beach Hotel Padang. The sampling technique in this research was Non Probability Sampling with the accidental sampling method and obtained a sampel of 372 respondents. The data used is primary data and secondary data. Data were collected in this research by distributing questionnaires, and the trial sampel for this research was 30 people. Instrument testing uses validity and reliability tests. The data analysis techniques in this research are data tabulation and data description.The results of the research that has been carried out show that the waiters at the Mentawai Restaurant Hotel Pangeran Beach Padang have good ethics (89%) and responsiveness (89%), however there are still 2 to 3% of waiters who do not have good ethics and responsiveness. The Prince Hotel should remind employees to have good ethics and responsiveness when working and provide training regarding etiquette and responsiveness with external sources from the hotel or company.